(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article discusses the issues of managing the risks of climate change impacts on viticulture in mountainous areas, the complexity of which requires a spatio-temporal study. The article chooses Vayots Dzor as an example, which is a typical mountainous area and is considered an ancient region rich in viticultural traditions. Here, there is a variety of interconnected agroclimatic conditions necessary for viticulture and obvious risks of climate change manifestations, which together make Vayots Dzor a typical object of geoecological research. Such research is not only of scientific and methodological interest and is useful for studying the agroclimatic conditions of other mountainous viticultural areas, but also, with its practical orientation, can contribute to the scientific understanding of the climate change problem observed in Vayots Dzor and risk management. The article presents the results of the calculation and analysis of the spatial-temporal distribution of agroclimatic resources in Vayots Dzor. The following main agroclimatic indices were used: the sum of active temperatures, the number of days with temperatures above 30℃, the average of absolute minimum temperatures, and the amount of precipitation during the vegetation period. As a result of the study, some changes in the agroclimatic conditions of the area over the past decades have been revealed, and agroclimatic areas favorable for viticulture have been identified. It has been found that within the scope of climate change resistance and adaptation risk management, there are new opportunities to expand the viticultural areas in Vayots Dzor and to develop the cultivation of valuable grape varieties.